Regional Analysis and Policy The Greek Experience - Coccossis, Harry; Psycharis, Yannis (Contributions to Economics, 2008)
Regional development is attracting the attention of policy makers and scientists again, as regions, urban centers and rural areas, experience substantial pressures, particularly in Europe, as a consequence of globalization and geopolitical changes which lead to changes in spatial structures and dynamics. This book is based on the contributions of Greek regional science research presented at the 2006 Congress of the European Regional Science Association at Volos, Greece. The contributions selected to be presented in this book address these changes offering a fresh look into regional development. They provide an overview of regional development concerns from Greek regional scientists but the issues discussed pervade Greek particularities and stimulate thinking about regional science, regional development and regional policy in the early twenty-first century.